Elementy spontaniczne i automatyczne w katalogach monarchów z okresu I Rzeczypospolitej - wstęp do charakterystyki gatunku (aspekt strukturalny) = Spontaneous and automatic elements in the catalogues of monarchs from the period of the First Republic - an introduction to the characteristics of genre (structural aspect) - Hawrysz, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to point out the fixed and variable generic elements in the former catolouges of monarchs within the structure of the text, that is, the clearest generic exponent of this form of expression, and thus attempt to establish a prototype of the genre. The article is based on the analyses of 11 works written in Polish created in the middle-Polish period.
Keywords: genologia; katalog władców; struktura gatunku; prototyp; elementy standardowe gatunku; elementy innowacyjne gatunku; genre studies; catalogues of monarchs; structure of a genre; prototype; conventional elements of a genre; innovative elements of a genre